Engineering problem solving with ANSI C : fundamental concepts - Etter, Delores M. (Englewood Cliffs, N.J. : Prentice Hall, 1995)
Engineering problem solving; Simple C programs; Control structures and data files; Modular programming with functions; Arrays and matrices; An introduction to pointers; Characters and text processing.
Includes bibliographical references and index.
Keywords: Computer program language; Engineering -- Data processing; C (Computer program language).